Sediments, morphology, and sedimentary processes on continental shelves : advances in technologies, research, and applications - Li, Michael; Sherwood, Christopher R.; Hill, Philip R.; International Association of Sedimentologists (Oxford : Wiley-Blackwell, 2012)
The application of multibeam and sediment transport measurement technologies and the adoption of multi-faceted research methodologies have greatly advanced our understanding of the sedimentary processes on continental shelves in the last decade. This book uniquely blends cutting-edge research and state-of-the art review articles that take stock of new advances in multibeam mapping and sediment transport technologies, spatial analysis and modelling, and the applications of these advances to the understanding of shelf sediments, morphodynamics, and sedimentary processes. Case studies are also presented to illustrate the utilization of seabed property and process knowledge in habitat mapping and ocean management. With its mix of papers focusing on technological advances, integration of shelf morphology and processes, and the application of these advances to coastal and ocean management, this Special Publication volume will serve as a milestone reference for professional marine scientists and as advanced text for students in marine geology, sedimentology and oceanography. This book is part of the International Association of Sedimentologists (IAS) Special Publications. The Special Publications from the IAS are a set of thematic volumes edited by specialists on subjects of central interest to sedimentologists. Papers are reviewed and printed to the same high standards as those published in the journal Sedimentology and several of these volumes have become standard works of reference.
P t. 1. Sediments and morphology in shelf and coastal systems -- pt. 2. Sediment transport processes, sedimentation and modelling -- pt. 3. Application and management.
Includes bibliographical references and index.
Print version record.
Keywords: Sedimentation and deposition; Sedimentology; Sediment transport; Continental margins; Continental margins; Sediment transport; Sedimentation and deposition; Sedimentology; Electronic books